2015
DOI: 10.1002/pola.27697
|View full text |Cite
|
Sign up to set email alerts
|

Postfunctionalization of polyoxanorbornene backbone through the combination of bromination and nitroxide radical coupling reactions

Abstract: The brominated backbone of poly(oxanorbornene imide) (PONB) (PONB-Br) was functionalized with 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO)-acrylate, -epoxy, and poly (ethylene glycol) (PEG) yielding PONB-acrylate, PONB-epoxy, and PONB-PEG through the nitroxide radical coupling (NRC) reaction. Although an excess amount of functional-TEMPOs were used. The observed NRC efficiencies were found in the range of 7-25%. Notably, 1 H NMR spectra of all polymers exhibited a signal at 6.08 ppm after NRC reactions indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The grafting‐through strategy was developed by the ROMP of a new ω‐ exo ‐norbornenyl PEO monomethyl ether macromonomer synthesized by NRC between a TEMPO‐containing norbornene and a bromoisobutyrate‐terminated PEO. In contrast with previous works that used the grafting‐onto strategy, herein the nitroxide moiety is anchored onto the polymer backbone and reacts with bromide‐functionalized PEO as the grafts. Moreover, the method reported in this work uses commercially available PEO graft precursors and thus, precludes the need for anionic polymerization of ethylene oxide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The grafting‐through strategy was developed by the ROMP of a new ω‐ exo ‐norbornenyl PEO monomethyl ether macromonomer synthesized by NRC between a TEMPO‐containing norbornene and a bromoisobutyrate‐terminated PEO. In contrast with previous works that used the grafting‐onto strategy, herein the nitroxide moiety is anchored onto the polymer backbone and reacts with bromide‐functionalized PEO as the grafts. Moreover, the method reported in this work uses commercially available PEO graft precursors and thus, precludes the need for anionic polymerization of ethylene oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Although ROMP of TEMPO‐containing norbornenes has been widely reported in the literature for organic‐electroactive materials or electron paramagnetic resonance (EPR) probes, few studies have been reported on the combination of ROMP and NRC to design graft copolymers. Complex architectures such as heterograft brush copolymers have been obtained from a ROMP‐generated polyoxanorbornene of number‐average degree of polymerization (trueitalicDPn¯) ranging from 9 to 20 with bromide pendant groups and TEMPO‐functionalized polymers according to a grafting‐onto strategy, with an efficiency ranging from 56 to 97% . While this work was in progress, the grafting‐through strategy has been used to synthesize brush polynorbornenes with a backbone of trueitalicDPn¯ up to 400 with polyacrylates and polystyrene grafts of trueitalicDPn¯ up to 40 from macromonomers obtained by a sequential atom transfer radical polymerization (ATRP)‐NRC strategy between a norbornene‐functionalized nitroxide radical and the halide chain‐end of ATRP polymers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, activated bromide‐containing substances are promising candidates for radical coupling reactions to realize polymer conjugation and periodic copolymer synthesis . In addition, even inactive bromides are reported to be capable of undertaking the aforementioned reactions . All of these contributions approve that polymers bearing activated bromides are ideal chemically modifiable platforms, and the toolbox includes a broad scope of substances.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] In addition, even inactive bromides are reported to be capable of undertaking the aforementioned reactions. 27,28 All of these contributions approve that polymers bearing activated bromides are ideal chemically modifiable platforms, and the toolbox includes a broad scope of substances. As a result, it is highly desired to develop mild and efficient modification protocol to ultimately increase the diversity of polymeric materials.…”
mentioning
confidence: 99%